The Perioperative Lung Transplant Virome: Torque Teno Viruses Are Elevated in Donor Lungs and Show Divergent Dynamics in Primary Graft Dysfunction. Issue 5 (4th November 2016) - Abbas, A. A.; Diamond, J. M.; Chehoud, C.; Chang, B.; Kotzin, J. J.; Young, J. C.; Imai, I.; Haas, A. R.; Cantu, E.; Lederer, D. J.; Meyer, K. C.; Milewski, R. K.; et al.
Abstract : Primary graft dysfunction (PGD) is a principal cause of early morbidity and mortality after lung transplantation, but its pathogenic mechanisms are not fully clarified. To date, studies using standard clinical assays have not linked microbial factors to PGD. We previously used comprehensive metagenomic methods to characterize viruses in lung allografts >1 mo after transplant and found that levels of Anellovirus, mainly torque teno viruses (TTVs), were significantly higher than in nontransplanted healthy controls. We used quantitative polymerase chain reaction to analyze TTV and shotgun metagenomics to characterize full viral communities in acellular bronchoalveolar lavage from donor organs and postreperfusion allografts in PGD and non‐PGD lung transplant recipient pairs. Unexpectedly, TTV DNA levels were elevated 100‐fold in donor lungs compared with healthy adults (p = 0.0026). Although absolute TTV levels did not differ by PGD status, PGD cases showed a smaller increase in TTV levels from before to after transplant than did control recipients (p = 0.041). Metagenomic sequencing revealed mainly TTV and bacteriophages of respiratory tract bacteria, but no viral taxa distinguished PGD cases from controls. These findings suggest that conditions associated with brain death promote TTV replication and that greater immune activation or tissue injury associated with PGD may restrict TTV abundance in the lung. Abstract : Investigation of the viral microbiome of donor organs and recipient allografts early after lung transplantation reveals that Torque teno viruses are markedly elevated in donor lungs prior to organ recovery, and perioperative viral dynamics differ in transplant recipients who experience primary graft dysfunction.